Oxotechnetium 99mTcO[SN(R)S][S] complexes as potential 5-HT1A receptor imaging agents. - Papagiannopoulou, D; Pirmettis, I; Tsoukalas, Ch; Nikoladou, L; Drossopoulou, G; Dalla, C; Pelecanou, M; Papadopoulou-Daifotis, Z; Papadopoulos, M.; Chiotellis, E (Nucl Med Biol, 2002)
A series of 99mTcO[SN(R)S][S] complexes carrying the 1-(2-methoxyphenyl)piperazine moiety on the tridentate ligand [SN(R)S] was synthesized. For structural characterization and for in vitro binding assays the analogous oxorhenium complexes were prepared. As demonstrated by appropriate competition binding tests in rat hippocampal preparations, all oxorhenium analogues showed affinity for the 5-HT(1A) receptor binding sites with IC(50) values at the nanomolar range (IC(50)= 5.8-103 nM). All 99mTcO[SN(R)S]/[S] complexes showed significant brain uptake in rats at 2 min p.i. (0.24-1.31% ID). However, a clear correlation between distribution of radioactivity in the brain and distribution of 5-HT(1A) receptors could not be established.
Keywords: Animals; Brain; In Vitro Techniques; Male; Organotechnetium Compounds; Radionuclide Imaging; Radiopharmaceuticals; Rats; Receptors, Serotonin; Receptors, Serotonin, 5-HT1; Rhenium; Tissue Distribution